Owner and Contractor Perceptions Toward Factors Causing Delays in Structural and Finishing Works - Andi A.; Lalitan D.; Loanata V.R. (Institute of Research and Community Outreach - Petra Christian University, 2010)
A construction project comprises of a number of work packages, which are subjected to delays. These delays may be caused by many on-site factors. The aim of this research is to represent owner and contractors perceptions towards delay factors that frequently occur in structural and finishing works. Data for analysis were gathered by distributing questionnaire. A total of 198 sets of questionnaire were gathered and used for subsequent analyses. In general, design changes during construction are perceived by respondents as the most frequent factor to cause delay in all structural and finishing works. The results also show that there are a number of differences between owner’s and contractor’s perceptions towards the occurrences of the factors. Whilst most contractors concern that information factors related to project design and scope frequently causing delays in construction works, owners consider many contractor originated factors, as most frequent delay causes.